Extracellular Vesicles in Mycobacterial Infections: Their Potential as Molecule Transfer Vectors - Wang, Jianjun; Wang, Yang; Tang, Lijun; Garcia, Rodolfo C. (Frontiers in Immunology, 2019)
Extracellular vesicles are membrane-bound structures released by living cells and present in body fluids. Their composition includes proteins, lipids, carbohydrates and nucleic acids and are involved in transfers between cells. Extracellular vesicles can deliver molecules to cells and tissues even if distant. As a consequence, they have a role in information transmission and in the modulation of the biological function of recipient cells. Among other things, they are involved in antigen presentation and the induction of secretion events by immune cells. Thus, extracellular vesicles participate in the regulation of immune responses during infections. We will discuss their potential as effectors and disease biomarkers concerning only mycobacterial infections.